2018
DOI: 10.3389/fimmu.2018.01098
|View full text |Cite
|
Sign up to set email alerts
|

Granulocytic Myeloid-Derived Suppressor Cells (GR-MDSC) in Breast Milk (BM); GR-MDSC Accumulate in Human BM and Modulate T-Cell and Monocyte Function

Abstract: Nosocomial bacterial infections (NBI) and necrotizing enterocolitis (NEC) are among the main reasons for death in preterm infants. Both are often caused by bacteria coming from the infected infant’s gut and feeding with breast milk (BM) seems beneficial in their pathogenesis. However, mechanisms causing the protective effect of BM are only incompletely understood. Myeloid-derived suppressor cells (MDSC) are myeloid cells with suppressive activity on other immune cells, recently described to play a role in medi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
18
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 27 publications
(20 citation statements)
references
References 55 publications
2
18
0
Order By: Relevance
“…These cells have been originally identified within the mononuclear cell fraction of patients with several types of solid tumours or haematological malignancies, but more recently they have also been found in a broad variety of acute and chronic inflammatory disease conditions, including infection with human immunodeficiency virus type 1, hepatitis B virus, or sepsis . Interestingly, immunosuppressive LDNs/PMN‐MDSCs have also been described in conditions in which an altered T‐cell tolerance is present, such as in pregnancy and breastfeeding, in neonates, or in healthy volunteers receiving G‐CSF for stem cell mobilization . As immunosuppressive LDNs/PMN‐MDSCs are composed by a mixture of immature and mature neutrophils, an open question is whether the suppressive cells correspond to the immature neutrophils or to the subpopulation of mature ones, which often display features of ‘activated/degranulated’ cells .…”
Section: Neutrophils and T Cellsmentioning
confidence: 99%
“…These cells have been originally identified within the mononuclear cell fraction of patients with several types of solid tumours or haematological malignancies, but more recently they have also been found in a broad variety of acute and chronic inflammatory disease conditions, including infection with human immunodeficiency virus type 1, hepatitis B virus, or sepsis . Interestingly, immunosuppressive LDNs/PMN‐MDSCs have also been described in conditions in which an altered T‐cell tolerance is present, such as in pregnancy and breastfeeding, in neonates, or in healthy volunteers receiving G‐CSF for stem cell mobilization . As immunosuppressive LDNs/PMN‐MDSCs are composed by a mixture of immature and mature neutrophils, an open question is whether the suppressive cells correspond to the immature neutrophils or to the subpopulation of mature ones, which often display features of ‘activated/degranulated’ cells .…”
Section: Neutrophils and T Cellsmentioning
confidence: 99%
“…Besides the accumulation of MDSC in the maternal organism during pregnancy as well as in the fetal and neonatal organism, recently our group could show that also breast milk contains large numbers of GR-MDSC ( 59 ). Numbers of GR-MDSC in breast milk from preterm infants correlated with gestational age (unpublished data).…”
Section: Mdsc In Breast Milkmentioning
confidence: 94%
“…Furthermore, we could show that breast milk GR-MDSC suppressed the expression of TLR-4 on monocytes. As putative mechanisms for MDSC-accumulation in breast milk, we investigated if prolactin or oxytocin could induce MDSC from PBMC, but could not show any effect ( 59 ). Beyond that, He et al showed that breastfed infants had increased GR-MDSC levels in comparison to infants fed with formula ( 51 ).…”
Section: Mdsc In Breast Milkmentioning
confidence: 99%
“…Milk samples were stored at 4 °C until further use and processed within six hours after collection. The isolation of milk cells was done as described previously [ 26 ]. Breast milk was diluted in a 1:1 ratio with phosphate-buffered saline (PBS, Biochrom, Berlin, Germany) and centrifuged for 20 min at 805× g .…”
Section: Methodsmentioning
confidence: 99%
“…Later, it was shown that MDSC and especially GR-MDSC also accumulate physiologically during pregnancy in the fetal and maternal organism [ 20 , 21 , 22 , 23 , 24 , 25 ], mediating materno-fetal tolerance. Recently, we could show that also BM contains a large population of GR-MDSC (BM-MDSC) [ 26 ], leading to the hypothesis that the transfer of BM-MDSC from mother to baby may influence the mucosal immunity of the newborn. However, to date, nothing is known about the content of GR-MDSC in BM of preterm infants.…”
Section: Introductionmentioning
confidence: 99%